(untitled) (Eurasian Scientific Herald, 2022)
In this article, the 7 most important principles of a healthy lifestyle, protection and promotion of the health of university students,the complexity of the transition period, the preservation of the purity of the environment and the preservation of mental and physiological qualities, optimal working capacity, social activity